PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BENGKULU - Aan Zulyanto (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
Since 2001, the Indonesian government has effectively run fiscal decentralization policy as a broad strategy to accelerate regional development. This study aims to see the influence of fiscal decentralization on economic growth in the province of Bengkulu. The analysis focused on indicators of fiscal decentralization of expenditure. And using a set of control variables consisting of the Initial Level Growth, Population Growth, Investment, and Human Capital. This study uses panel data and analytical tools of LSDV or Fixed Effects Model (FEM). The study shows that there is a hump-shaped form in the influence of fiscal decentralization in the province of Bengkulu. This means that when the degree of fiscal decentralization is not too high, then the fiscal decentralization policy will bring positive impact on economic growth, but the degree of decentralization is too high, fiscal decentralization policies will only hinder economic growth.